A particular frozen yogurt has 75 cal in 2 ounces how many calories are in 8 ounces of the yogurt

Answers

Answer 1
Answer:

Total number of calories in 8 ounce yogurt is 300 calories.

Given that;

Total number of calories in 2 ounce yogurt = 75 calories

Find:

Total number of calories in 8 ounce yogurt

Computation:

Total number of calories in 8 ounce yogurt = 75[8/2]

Total number of calories in 8 ounce yogurt = 75[4]

Total number of calories in 8 ounce yogurt  = 300 calories

Learn more:

brainly.com/question/22374134?referrer=searchResults

Answer 2
Answer: Just divide 8 by 2 and you'll get 4
Each container is 2 ounces so do 75 times 4 and you'll get 300 calories

Related Questions

You have a coupon for a restaurant. You save $3 on a meal. What was the original cost of the meal?
Given f(x)=10x over 2+7, find f^-1(x)I have provided a picture of the equation for it to be easier to read
Marking as Brainiest!!!!!
Mark made a smoothie using the following ingredients, 1 1/4 cups of strawberries, 2 2/4 cups of vanilla yogurt, 1/2 cup of orange juice, and 2 1/2 cup of strawberry yogurt. What is the total amount of yogurt Mark used in the smoothie? * 1 point 3 cups 2 3/6 cups 5 cups 1 ¼ cups
Simplify the given equation.17x - 6 + 3x - 5 = x + 11 + 4x

Evaluate if c=3 and d=-4 2c/d

Answers

Substitute 3 into the expression for c and -4 for d. So, 2c/d = 2(3)/(-4) = 6/-4 = -3/2.  The answer is -3/2.

What is (4-5a)^2 - a (2a -3)

Answers

23a²+-37a+16 is the answer

3a^2+13 should be correct

If f(1)=3 and f(n)=-2f(n-1)+1,then f(5)=

Answers

The value f(5) when f)1) = 3 is f(5) = 43.

How to find the 5th term of the sequence?

The fifth term of the sequence can be found by finding the value of all the terms that precede it.

We can find the value of f(5) as shown below:

The value of f(1) is given as:

f(1) = 3

With this, we can find the value of f(2) and with f(2), we can find the value of f(3), and so on.

f(n) = - 2f(n-1)+1

At n = 2:

f(2) = -2f(2-1)+1

= - 2f(1)+1

= - 2*3 + 1

= - 5

When n = 3:

f(3) = -2*-5 + 1

= 11

When n = 4:

f(4) = -2*11 + 1

= -21

When n = 5:

f(5) = -2*-21 + 1

= 43

Therefore, we have found the value of f(5) to be f(5) = 43.

Learn more about sequences here: brainly.com/question/6561461

#SPJ2

f(5) = - 2f(4) + 1
f(4) = -2f(3) + 1
f(3) = -2f(2) + 1
f(2) = -2f(1) + 1
Therefore:
 f(2) = -2(3) + 1 = -5
f(3) = -2(-5) + 1 = 11
f(4) = -2(11) + 1 = -21
Therefore f(5) = -2(-21) + 1 = 43

Javier drove 45 miles, this represents 60% of his entire trip. What is the total number of miles in his trip

Answers

Ratio and proportion

45mi/60%=x miles/100%
cross multiply
60x=4500
   x=75 miles

hope this helps
60% is the same thing as 6/10, or 3/5. So 45 miles is 3/5 of his trip. 45=3/5x, where x is the number of miles in his trip. Divide both sides by 3/5 and you should get 75 miles.

Perpendicular Vectors:Find v x w if v=5i -4j +4k & w=-6i +3j -2k.
A. 3i-4j-2k
B. -14i-9j-4k
C. 5i +3j -4k
D. -4i -14j -9k

Find v x w if v=-3i-4j-8k & w=2i+6j+4k.
A. 12i -2j +3k
B. 8i +12j +32k
C. 32i -4j -10k
D. 10 i -8j +3k

Find the cross product <-6, 7, 2> x <8, 5, -3>. Is the resulting vector perpendicular to the given vectors?
A. <-31,-2,-86>;yes
B. <-37,-2,0>; no
C. <0,-86,-37>; yes
D. <-37, 0, -80>;no

Answers

1.
v x w = 8 i - 24 j + 15 k + 10 j - 12 i - 24 k =
= - 4 i - 14 j - 9 k
Answer: D )
2.
v x w = -16 i - 16 j - 18 k + 12 j + 48 i - 8 k =
= 32 i - 4 j - 10 k
Answer: C )
3.
The cross product:
< - 6, 7, 2 > x < 8, 5, -3 > =
= - 21 i + 16 j - 30 k - 18 j - 10 i - 56 k =
= - 31 j - 2 j - 86 k = < - 31, - 2, - 86 >
Vectors are perpendicular if: cos ( u, v ) = 0
< - 6 , 7. 2 > * < -31, - 2, - 86 > = 186 - 14 - 172 = 0
< 8, 5 , - 3 > * < - 31, - 2, - 86 > = -248 - 10 + 258 = 0
Answer: A ) < - 31, - 2 , - 86 >,  yes.

Verify
tanx + cotx = 1/ sinxcosx

Answers

\textit{Pythagorean Identities} \n\n sin^2(\theta)+cos^2(\theta)=1 \n\n[-0.35em] \rule{34em}{0.25pt}\n\n tan(x )+cot(x )~~ = ~~\cfrac{1}{sin(x )cos(x)} \n\n[-0.35em] ~\dotfill\n\n tan(x )+cot(x )\implies \cfrac{sin(x)}{cos(x)}+\cfrac{cos(x)}{sin(x)} \n\n\n \cfrac{sin^2(x)+cos^2(x)}{sin(x )cos(x)}\implies \cfrac{1}{sin(x )cos(x)}